Pathological phenotype in familial neurodegenerative disease: implications for families and therapeutic constructs. Issue 5 (September 2011) - Castellani, Rudy J; Lee, Hyoung-gon; Petersen, Robert B; Zhu, Xiongwei; Perry, George
Most major subtypes of neurodegenerative disease are comprised of common sporadic, age-related conditions, by definition lacking germline mutation, and rare familial autosomal dominant conditions, referred to by the same name owing to a similar phenotype. Familial cases are traditionally viewed as critically important to the understanding of disease pathogenesis, since singular genes and limited protein transcripts of presumed importance can be isolated and closely studied. For the same reason, animal models are more readily generated, either by overexpression of a germline mutation for example, or genetic manipulation to produce a construct with a number of mutations. Moreover, the underlying central purpose for such experimental constructs is to provide a homolog to human disease that can be studied in terms of pathogenesis, and, more importantly, therapeutic intervention. The fact that they are based on rare Mendelian conditions is never raised in terms of relevance to sporadic disease. In light of therapeutic failures in neurodegenerative diseases across the board, re-examination of the issue of familial disease, its accompanying pathology and its consistency with sporadic disease may be in order, as it may not be valid to design a new therapy based on a familial construct and then apply that therapy to the sporadic disease.